Perencanaan Strategis Sistem Informasi Sekolah Musik Dengan Metode Ward and Peppard dan Anita Cassidy - Kanggep, Kanggep Andrijana Kusuma; Naufal, Alman; Ratna Juwita Sari, Deassy; Dwicahya Supriatman, Rian; Maulani, Shanti (Jurnal Sistem Informasi Galuh, 2024)
The music school business is very suitable for implementing an information system strategy because one of its goals is related to customer satisfaction which requires a business strategy that can support the achievement of organizational goals. So it is deemed necessary to have strategic information system planning to increase business competitiveness for music schools. The research carried out aims to analyze the situation of music schools, to be able to provide suggestions for information system strategies that are efficient and effective in achieving organizational goals in music schools. In this research, the author made direct observations at one of the music schools is Majestic Symphony Music School Bandung to obtain data, documents, and conducted interviews with business people as sources of information needed by the author. The approach used to develop the framework for this research, the author uses Ward and Peppard and Anita Cassidy. The final result of this research is strategic planning for information systems and information technology for music schools in the form of information system application needs. Plans for changes in organizational structure, information technology infrastructure needs, Information Systems and Information Technology Portofolio in the future as well as Strategic Plans for Information Systems and Information Technology for music schools. The suggestion from this research is that adequate human resources must be prepared before the new system is used and testing has been carried out on the new system before it is decided to operate.